Pelatihan Membuat Soal dengan Google Form Untuk Tenaga Pendidik dan Tenaga Kependidikan di SDN Sukaresmi 02 Kabupaten Bekasi - Niantoro Sutrisno; Faridah Faridah; Ria Estiana; Nurul Giswi Karomah; Taty Noorhayati (Yayasan Literasi Sains Indonesia, 2022)
Since the Covid-19 outbreak, many learning activities have been carried out online. Learning uses online media, exam questions can be made using technology that utilizes the internet as a medium, such as using the Google Form application. Besides that, Google Forum has a feature that is easy to use for uploading and downloading questions and answers. This community service is carried out with the aim of adding insight and increasing technological skills to educators and education staff in utilizing the Google form to make questions. The methods used in community service activities are lectures, demonstrations and questions and answers. The conclusions that can be drawn from this training activity are 1) it can increase the knowledge and insight of teachers and employees in understanding the Google form application as a medium for making questions. 2) Improve skills in applying google form media. 3) Increasing the ability of educators and educational staff in carrying out learning activities and using the Google Form application to help smooth learning activities in schools.